2019
DOI: 10.1038/s41419-019-1895-4
|View full text |Cite
|
Sign up to set email alerts
|

Degraded neutrophil extracellular traps promote the growth of Actinobacillus pleuropneumoniae

Abstract: Actinobacillus pleuropneumoniae (A.pp) causes severe pneumonia associated with enormous economic loss in pigs. Peracute diseased pigs die in <24 h with pneumonia. Neutrophils are the prominent innate immune cell in this infection that massively infiltrate the infected lung. Here we show that neutrophils release neutrophil extracellular traps (NETs) as response to A.pp infection. Numerous NET-markers were identified in bronchoalveolar lavage fluid (BALF) of A.pp-infected piglets in vivo, however, most NET fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 47 publications
3
66
0
1
Order By: Relevance
“…The authors observed an enhanced bacterial clearance in the CSF of infected rats by increased phagocytosis and NET degradation when treated with DNase 1. In contrast to this protective effect of DNase 1 in meningitis, it was found that the respiratory tract pathogens Actinobacillus pleuropneumoniae and Haemophilus influenzae survive even better in the presence of neutrophils treated with DNases, because degraded NETs release nutrients as NAD, which enhance bacterial growth [12].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The authors observed an enhanced bacterial clearance in the CSF of infected rats by increased phagocytosis and NET degradation when treated with DNase 1. In contrast to this protective effect of DNase 1 in meningitis, it was found that the respiratory tract pathogens Actinobacillus pleuropneumoniae and Haemophilus influenzae survive even better in the presence of neutrophils treated with DNases, because degraded NETs release nutrients as NAD, which enhance bacterial growth [12].…”
Section: Introductionmentioning
confidence: 92%
“…A Pico Green quantification assay (Quant-iT™ PicoGreen ® ; Invitrogen, Carlsbad, CA, USA) was performed to determine free DNA in CSF and serum, as described previously [12].…”
Section: Pico Green Quantification Assaymentioning
confidence: 99%
“…Paraffin-embedded organs from Section 4.1 were cut into 4 µm sections and stretched on SuperFrost Plus™ adhesion slides (Thermo Fisher Scientific GmbH, Germany). Samples were deparaffinized and handled as previously described [68]. Briefly, the samples were incubated at room temperature for 1 h with primary antibodies diluted in blocking buffer.…”
Section: Staining Of Nets In Histological Slicesmentioning
confidence: 99%
“…This application did not alter the capacity of porcine neutrophils to release NETs or their MPO activity in response to PMA, ionomycin, or zymosan [67]. Interestingly, it has recently been shown that degraded neutrophil extracellular traps promote the growth of Actinobacillus pleuropneumoniae (A.pp) [130], an important porcine pathogen leading to high economic loss [131]. A.pp, itself, releases no nuclease, but the authors identified host nucleases as a source that degrades NETs after A.pp infection [130].…”
Section: Extracellular Traps In Suidaementioning
confidence: 88%
“…Interestingly, it has recently been shown that degraded neutrophil extracellular traps promote the growth of Actinobacillus pleuropneumoniae (A.pp) [130], an important porcine pathogen leading to high economic loss [131]. A.pp, itself, releases no nuclease, but the authors identified host nucleases as a source that degrades NETs after A.pp infection [130]. These data shed light on the detrimental effects of NETs during a host immune response against certain bacterial species that require or efficiently take advantage of degraded DNA material which has been provided by host nuclease or nucleases of other coinfecting bacteria as a source of growth-aiding nutrients.…”
Section: Extracellular Traps In Suidaementioning
confidence: 99%